2014
DOI: 10.6018/analesps.30.1.165371
|View full text |Cite
|
Sign up to set email alerts
|

Síntomas psicopatológicos en adolescentes españoles: relación con los estilos parentales percibidos y la autoestima

Abstract: Resumen: El objetivo de esta investigación fue analizar la sintomatología psicopatológica evaluada con el SCL-90-R en una muestra comunitaria de 935 adolescentes españoles y su interacción con el estilo parental percibido y la autoestima. La muestra estuvo compuesta por 489 chicos y 446 chicas de edades comprendidas entre los 12 y 18 años (M = 14.84, DT = 1.83) que cursaban estudios de Educación Secundaria y Bachillerato. Catorce centros de la Región de Murcia y Castilla-La Mancha aceptaron participar en el es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
4
20
0
3
Order By: Relevance
“…Self-disclosure is the dimension that is most closely related to these three antisocial behavior variables. These results are consistent with previous studies that use the original version of the parenting style questionnaire by Oliva et al (2007): the same pattern of results regarding the external problems and substance abuse variables (Oliva et al, 2007) and hostility (Rosa-Alcázar et al, 2014) variables is found. Calvete et al (2014) use only the affection and communication factor in their study, finding that it is a significant protective factor of both physical and psychological aggression against fathers and mothers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Self-disclosure is the dimension that is most closely related to these three antisocial behavior variables. These results are consistent with previous studies that use the original version of the parenting style questionnaire by Oliva et al (2007): the same pattern of results regarding the external problems and substance abuse variables (Oliva et al, 2007) and hostility (Rosa-Alcázar et al, 2014) variables is found. Calvete et al (2014) use only the affection and communication factor in their study, finding that it is a significant protective factor of both physical and psychological aggression against fathers and mothers.…”
Section: Discussionsupporting
confidence: 92%
“…The internal consistency for the scores in each factor is high. The alpha values obtained for each factor are similar and in some cases even higher than those found in the original scale (Oliva et al, 2007; Sabán et al, 2013; Calvete et al, 2014; Rosa-Alcázar et al, 2014; Gómez-Ortiz et al, 2015). Therefore, reducing the items by factor to four does not seem to have negatively affected factor internal consistency.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…At any rate, these results draw particular attention as low self-esteem and body dissatisfaction seem to constitute risk factors for suffering disorders related to body image (Espina, Ortego, Ochoa, Yenes, & Alemán, 2001;Raich, 2004), while parenting styles that are perceived as positive tend to have a significant negative relationship with psychopathological symptoms (Rosa-Alcázar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that Muris et al (19) did not find any association between parenting styles and internalizing behaviors, Rosa-Alcazar et al (23), stated that girls show fewer symptoms and a more adaptive perception of parenting styles, compared to boys.…”
Section: Introductionmentioning
confidence: 94%